2015
DOI: 10.1515/pjfns-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the In Vitro Inhibitory Activity of Rye-Buckwheat Ginger Cakes with Rutin on the Formation of Advanced Glycation End-Products (AGEs)

Abstract: In this study, the relationship between the inhibitory effects of extracts from rye-buckwheat ginger cakes supplemented with low and high rutin dosage baked without or with dough fermentation step on the formation of fluorescent advanced glycation end-products (AGEs), and phenolic compounds, rutin, D-chiro-inositol and antioxidant capacity were addressed. The cakes were based on rye flour substituted by light buckwheat flour or flour from roasted buckwheat groats at 30% level, and were produced with or without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The correlation studies demonstrated that the inhibitory effects of analyzed samples against the formation of AGEs were correlated with their bioactive compound contents (for free fractions: TPC/AGEs inhibition, r = 0.77; the sum of phenolic acid/AGEs inhibition, r = 0.83; the sum of flavonoids/AGEs inhibition, r = 0.94; and for bound fractions: TPC/AGEs inhibition, r = 0.53; the sum of phenolic acid/AGEs inhibition, r = 0.55; the sum of flavonoids/AGEs inhibition, r = 0.72) and AC (ABTS assay/AGEs inhibition, r = 0.60; DPPH assay/AGEs inhibition, r = 0.95) determined in the samples. Our data on the anti-glycation effect are in agreement with the previously published research [ 54 , 59 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The correlation studies demonstrated that the inhibitory effects of analyzed samples against the formation of AGEs were correlated with their bioactive compound contents (for free fractions: TPC/AGEs inhibition, r = 0.77; the sum of phenolic acid/AGEs inhibition, r = 0.83; the sum of flavonoids/AGEs inhibition, r = 0.94; and for bound fractions: TPC/AGEs inhibition, r = 0.53; the sum of phenolic acid/AGEs inhibition, r = 0.55; the sum of flavonoids/AGEs inhibition, r = 0.72) and AC (ABTS assay/AGEs inhibition, r = 0.60; DPPH assay/AGEs inhibition, r = 0.95) determined in the samples. Our data on the anti-glycation effect are in agreement with the previously published research [ 54 , 59 ].…”
Section: Resultssupporting
confidence: 93%
“…Dietary advanced glycation end products (AGEs) are formed in thermally treated foods as a result of the Maillard reaction. These products are essential to the total pool of AGEs produced in the living organism [ 54 ]. The inhibitory effects of the elder products and gingerbread cookies evaluated by the BSA-glucose model are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polyphenols quercetin and rutin were shown to be mainly responsible for the high inhibitory properties of this herb. Therefore, it was said that these polyphenols do not bind to proteins, but rather, react through the formation of adducts with MGO [34]. The AGE inhibitory activity of Houttuynia cordata was shown to be 2–3 times higher than that of aminoguanidine; however, Yoon and Shim [33] incubated samples for three weeks, so the time of incubation might have led to the better inhibitory activity in this case.…”
Section: Resultsmentioning
confidence: 99%
“…However, Jiao et al (2019) reported phenolic compounds also to promote AGEs formation in an inappropriate oxidant environment because hydrogen peroxide is generated by autoxidation of phenolic compounds. Similarly, some phenolic compounds reported to have AGEs inhibition effect in rye‐buckwheat ginger cake (Przygodzka & Zielinski, 2015) showed no inhibitory effects on AGEs formation in sponge cake (Srey et al, 2010). These results indicated that the AGEs reduction strategy should be applied differently depending on the food types and process.…”
Section: Introductionmentioning
confidence: 97%